A COMPARATIVE EVALUATION OF CHATGPT, GEMINI, AND PERPLEXITY FEEDBACK FOR B1-B2 EFL LEARNERS - Kasimova, Malika; Babakulova, Dilrabo (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
In recent years, Artificial Intelligence (AI) has become an increasingly influential component of educational practice, particularly in language learning. AI-powered tools are now capable of offering immediate, personalized, and contextually sensitive support, helping learners develop writing accuracy, critical thinking, and revision strategies. In EFL contexts, AI enhances access to highquality feedback and reduces teachers’ workload by automating lower-level tasks, allowing instructors to focus on formative guidance. This study investigates the expanding role of AI in EFL writing instruction, with a special focus on grammar feedback generated by ChatGPT, Gemini, and Perplexity. The case study involved 16–17-year-old learners from a military-academic lyceum, representing B1–B2 proficiency levels. Using researcher-designed rubrics, AI-generated feedback was evaluated across three key dimensions: technical accuracy, pedagogical clarity, and linguistic appropriacy. The results show that ChatGPT provides human-like, detailed, and supportive explanations that foster understanding, while Gemini delivers concise and structured feedback that suits more autonomous learners. Perplexity, in contrast, offers factual but brief comments, emphasizing accuracy over elaboration. These findings suggest that while AI tools can enhance feedback speed and consistency, their pedagogical value depends heavily on teacher mediation and careful prompt design. The study concludes that AI should not replace the teacher’s role but rather complement it acting as a co-pilot that supports learners through timely, personalized guidance. The research contributes to AI-informed pedagogy by linking feedback theory, rubric-based evaluation, and classroom practice.